2013
DOI: 10.1016/j.nonrwa.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis and numerical simulation of pattern formation under cross-diffusion

Abstract: a b s t r a c tCross-diffusion driven instabilities have gained a considerable attention in the field of population dynamics, mainly due to their ability to predict some important features in the study of the spatial distribution of species in ecological systems. This paper is concerned with some mathematical and numerical aspects of a particular reaction-diffusion system with cross-diffusion, modeling the effect of allelopathy on two plankton species. Based on a stability analysis and a series of numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…In developmental biology, recent experimental findings demonstrate that cross-diffusion can be quite significant in generating spatial structure [10]. The effects of cross-diffusion on models for pattern formation (i.e., reaction-diffusion type) have been studied in many theoretical papers [13][14][15][16][17][18][19][20][21][22][23][24]. Recently, in [25] we showed that introducing cross-diffusion to a system of reaction-diffusion equations results in further relaxation of the conditions necessary for the emergency of patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In developmental biology, recent experimental findings demonstrate that cross-diffusion can be quite significant in generating spatial structure [10]. The effects of cross-diffusion on models for pattern formation (i.e., reaction-diffusion type) have been studied in many theoretical papers [13][14][15][16][17][18][19][20][21][22][23][24]. Recently, in [25] we showed that introducing cross-diffusion to a system of reaction-diffusion equations results in further relaxation of the conditions necessary for the emergency of patterns.…”
Section: Introductionmentioning
confidence: 99%
“…An important number of contributions have been proposed to treat systems like (1.1) from a numerical perspective, either considering or not the cross-diffusion effect (see [2,5,6,8,14,18,21,39] for finite differences, finite volumes, spectral and finite element methods for the spatial discretization). Here, and following [11,27,37], we propose a new finite volume element (FVE) method for the numerical approximation of the underlying reaction-cross-diffusion system.…”
Section: Introductionmentioning
confidence: 99%
“…That is, we require that the positive equilibrium point u * is linearly stable in the absence of the cross-diffusion but unstable in the presence of cross-diffusion. For this, we first introduce the following notations [Tian et al, 2011;Ruiz-Baier & Tian, 2013]. Let 0 = µ 1 < µ 2 < · · · → ∞ be the eigenvalues of −∇ 2 on Ω under no-flux boundary conditions and E(µ i ) be the space of eigenfunctions corresponding to eigenvalue µ i .…”
Section: Theoretical Analysis Of Dynamical Behaviorsmentioning
confidence: 99%
“…A two-species model with cross-diffusion in the context of plasma physics and predator-prey dynamics was also proposed and studied [del-Castillo-Negrete et al, 2002;del-Castillo-Negrete & Carreras, 2002]. It was shown that in the predator-prey system, mutual diffusion can induce Turing instability to produce spatial patterns even though a spatial homogeneous equilibrium state in the absence of one cross-diffusion is stable [Tian et al, 2011;Ruiz-Baier & Tian, 2013;Xue, 2012;Wang et al, 2010]. In addition, in chemical reaction systems, cross-diffusion can arise from interactions between the species and occurs in, e.g.…”
Section: Introductionmentioning
confidence: 99%